Smarcd3 is an epigenetic modulator of the metabolic landscape in pancreatic ductal adenocarcinoma - L. Paige Ferguson; Jovylyn Gatchalian; Matthew L. McDermott; Mari Nakamura; Kendall Chambers; Nirakar Rajbhandari; Nikki K. Lytle; Sara Brin Rosenthal; Michael Hamilton; Sonia Albini; Martin Wartenberg; Inti Zlobec; et al. (Nature Communications, 2023)
Clinical management of pancreatic cancer remains challenging. Here, the authors suggest SMARCD3 as a potential epigenetic dependency establishing the metabolic landscape in aggressive pancreatic cancer cells and as a potential therapeutic target in pancreatic cancer.